Cervical Spine Osteomyelitis and Epidural Abscess after Chemoradiotherapy for Hypopharyngeal Carcinoma: A Case Report - Yushi Ueki; Jun Watanabe; Shigehisa Hashimoto; Sugata Takahashi (Case Reports in Otolaryngology)
Osteomyelitis of mandible as a delayed adverse event following radiation therapy has been widely reported; however, osteomyelitis of the cervical spine has rarely been reported. In this study, we reported our experience with a case of cervical spine osteomyelitis and epidural abscess after concurrent chemoradiotherapy (CCRT) for hypopharyngeal carcinoma. The case involved a 68-year old man who underwent radical CCRT after a diagnosis of stage IVb, T4bN2cM0 posterior hypopharyngeal wall carcinoma. At 7 months after completing the initial therapy, the patient complained of severe pain in the neck and both shoulders and reduced muscular strength in the extremities. A large defect was found on the mucosa of posterior hypopharyngeal wall. On cervical magnetic resonance imaging, cervical spine osteomyelitis and an epidural abscess were observed. Because antimicrobial therapy was not effective, hyperbaric oxygen therapy was administered. Abscess reduction and improvement of the mucosal defect were observed. Because cervical spine complications after CCRT can be fatal upon worsening, adequate attention must be given.